Experimental investigation of membrane distillation with bubble column dehumidifier system for water desalination. (November 2022) - Hussein, Adel; Khalifa, Atia E.; Alawad, Suhaib M.; Antar, Mohamed A.
Abstract: The performance of a new integrated system of single-stage sweeping gas membrane distillation module and a bubble column dehumidifier (SGMD-BCD) was experimentally investigated. The productivity and energy consumption of the system is evaluated under different operating conditions. The SGMD module acts as a humidifier to produce high-quality distilled and the bubble column dehumidifier is an effective condenser for improved performance. The sweeping air stream is created in two different ways; using a vacuum pump and compressed air. Results showed that the integrated system yields higher permeate flux, better gained output ratio (GOR), and lower specific thermal energy consumption (SEC) when the vacuum pump is used. Increasing the feed temperature from 50 to 80 °C increased the flux by 175%, on average. Doubling the sweeping air flow rate from 1 to 2 SCFM resulted in flux enhancement of 49% and 25% for the vacuum pump and the compressed air supply, respectively. Operating the system with the vacuum pump and without cooling the bubble column dehumidifier showed a marginal reduction in flux but resulted in significant improvements in GOR and SEC values of 0.76 and 909 kWh/m 3, respectively, at an optimum dehumidifier water column height of 9.5 cm.